Perkuatan pada Balok Beton Berlubang di Daerah Tekan yang Mengalami Lenturan dengan Mortar Geoplimer - Karjanto , Adjib; Djatmika, Boedya; Susanto, Prijono Bagus (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2019)
In its development, changes in building functions often occur so as to require flexible bending of building functions, ways are needed to provide reinforcement or repairs to hollow beams. One method in strengthening or repairing hollow beams is the grouting method. Grouting using geopolymer material has the advantage of great strength and faster setting time. These geopolymer properties are very suitable for grouting methods that require fast setting times and small shrinkage. In this study the test uses a beam measuring 100 X 20 X 15 cm with 10 M NaOH molarity Comparison of the activator, as well as the location and number of holes, 2 points in the bending area to determine the flexural strength and condition of the concrete after reinforcement (grouting). Where in this study used 9 pieces of reinforced concrete beams (3 normal beams, 3 porous beams, 3 reinforced beams). Normal beams have an average bending capacity of 149.777 kg / cm2, while hollow beams have an average bending capacity of 118.36 kg / cm2, and repaired / grouting beams have an average bending capacity of 139.022 kg / cm2. There is a difference in the average flexural capacity in normal beams of 149.777 kg / cm2 in hollow beams of 118.36 kg / cm2, which has a difference of 31.41 kg / cm2 (20.97%). There is a difference in the average flexural capacity in the grouting beam of 139.022 kg / cm2 in the hollow beam of 118.36 kg / cm2, which has a difference of 20.66 kg / cm2 (14.86%). In a statistical analysis with a significance of 0.05 there was no significant difference in flexural strength in reinforced concrete grouting blocks 131.11 kg / cm2 against normal beams, 149.77 kg / cm2 had a difference of 10.755 kg / cm2 in a percentage of 7.19%.